IT VALUE ANALYSIS : THE CASE STUDY OF PT. BANK TABUNGAN NEGARA, TBk - Harvard K. Najoan; Festus Evly R.I. Liow (CV. Adiba Aisha Amira, 2024)
Information Technology (IT) has significantly influenced the operations and strategies of most organizations and industries now days. Computer, telecommunications and computer based information systems have been taking a major part of business process to increase competitive advantage as a Resource Based View theory purposes. To confirm this theory, a case study is performed for PT. Bank Tabungan Negara, Tbk., one of the largest bank in Indonesia engaged primarily in housing finance. Researched data refer to Bank Tabungan Negara Annual report published between 2011, 2012 and 2013. The study focuses on data that have relationship between IT expenditure and business performance. Result shows that IT spending gave a significant positive result. Bank Tabungan Negara IT resources analyzed in term of IT capability, IT competence and competitive advantage that lead to be the IT value model. In conclusion, the case study resulting that IT value positively affected Bank Tabungan Negara business performance.